1993
DOI: 10.7557/2.13.4.1120
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey of three virus infections in reindeer in northern Norway and Svalbard

Abstract: Sera from 326 Norwegian reindeer (NR) and from 40 Svalbard reindeer (SR) were examined for antibodies to reindeer herpesvirus (RHV), bovine viral diarrhoea virus (BVDV) and parainfulenza type 3 virus (PIV-3). No antibodies to any of these three viruses were detected in sera from SR. Sixty-three percent of sera from 101 adult NR (> 12 months old) and 15% of 225 NR calves (6 months old) had antibodies to RHV; corresponding values for BVDV were 41% and 6%, respectively. Twenty-seven percent of adult NR and 1% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 3 publications
4
23
2
Order By: Relevance
“…Several serological studies of CvHV-2 infection in reindeer that have been carried out in the past 10 to 20 years have confirmed a widespread distribution for alphaherpesvirus infections in semidomesticated reindeer (31,36). Nonetheless, alphaherpesviruses have not been isolated from reindeer in Norway or detected by PCR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several serological studies of CvHV-2 infection in reindeer that have been carried out in the past 10 to 20 years have confirmed a widespread distribution for alphaherpesvirus infections in semidomesticated reindeer (31,36). Nonetheless, alphaherpesviruses have not been isolated from reindeer in Norway or detected by PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally it has been demonstrated that CvHV-2 can infect bovines and cause a mild rhinotracheitis, but no latency of CvHV-2 has been detected in bovines (18,34). Serological evidence of CvHV-2 infection has been reported for both wild (13) and semidomesticated (31,36) reindeer (Rangifer tarandus tarandus) in Norway, for barren-ground caribou (Rangifer tarandus groenlandicus) in Greenland (4), and for Grant's caribou (Rangifer tarandus granti) in Alaska (8).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…However, in a serological survey in reindeer in Norway all 326 sera tested for antibodies against PIV-3 were negative (Stuen et al, 1993).…”
Section: Parainfluenza Type 3 Virus (Piv-3) Infection Piv-3 Commonly mentioning
confidence: 99%
“…In France, Baradel et al (1988) determined an antibody prevalence of 0.7% in roe deer, 5.5% in chamois and 7.5% in ibex. Seropositive reindeer were found by Stuen et al (1993) in Norway (9%) and by Rehbinder et al (1992) in Sweden (6%). In the former WestGermany, antibodies against BVDV have been found in approximately 7% of red deer (Weber et al, 1978, 6.6%; Frolich, 1993, 7.7%), and in roe deer (Weber et al, 1978, 5.9 %; Frolich, 1993, 10%).…”
Section: Introductionmentioning
confidence: 99%